KONSEP DAKWAH BIL HAL DALAM MAJELIS TAKLIM DIMASJID AL-AMINIYAH SUDIMARA PINANG KOTA TANGERANG - Khaisar Masrul; Ahmad Saiful Bahri (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
The concept of da'wah Bil Hal in the taklim assembly in the mosque al-aminiyah Sudimara Pinang Tangerang City. In that context. The author intends to answer the basic question of how the implementation of the concept of da'wah is implemented. More specifically, the author will examine the first three questions, how the history that affects the congregation is hindered by 'Isha' prayer at the beginning of time. Second, what underlies the objectives of political identity and critical pluralism in the assembly. Third, how the views and effects of the talk were to the worshippers. In the media student's book fifth edition Gill Branston and Roy Stafford in 2010. The author will analyze with three concepts in the book. The concept is after Marxism, identity politics and pluralism kritits and lectures. In his analysis has answered three minor questions. Awareness in Muslims increases the science and worship of amaliyah. In conclusion in this paper can be put forward the following: first, Islam is the religion of da'wah. Second, Islam unites people socially and realizes a dignified society (Khaira Ummah). Third, do not waste time in praying Fardhu. Fourth, knowledgeable religion also has cultural intelligence. Fifth, do the righteous and leave the evil.